TMS with fast and accurate electronic control: measuring the orientation sensitivity of corticomotor pathways - Souza, Victor H; Nieminen, Jaakko O; Tugin, Sergei; Koponen, Lari M; Baffa, Oswaldo; Ilmoniemi, Risto J (bioRxiv, 2021)
Background: Transcranial magnetic stimulation (TMS) coils allow only a slow, mechanical adjustment of the stimulating electric field (E-field) orientation in the cerebral tissue. Fast E-field control is needed to synchronize the stimulation with the ongoing brain activity. Also, empirical models that fully describe the relationship between evoked responses and the stimulus orientation and intensity are still missing. Objective: We aimed to (1) develop a TMS transducer for manipulating the E-field orientation electronically with high accuracy at the neuronally meaningful millisecond-level time scale and (2) devise and validate a physiologically based model describing the orientation selectivity of neuronal excitability. Methods: We designed and manufactured a two-coil TMS transducer. The coil windings were computed with a minimum-energy optimization procedure, and the transducer was controlled with our custom-made electronics. The electronic E-field control was verified with a TMS characterizer. The motor evoked potential amplitude and latency of a hand muscle were mapped in 3° steps of the stimulus orientation in 16 healthy subjects for three stimulation intensities. We fitted a logistic model to the motor response amplitude. Results: The two-coil TMS transducer allows one to manipulate the pulse orientation accurately without manual coil movement. The motor response amplitude followed a logistic function of the stimulus orientation; this dependency was strongly affected by the stimulus intensity. Conclusion: The developed electronic control of the E-field orientation allows exploring new stimulation paradigms and probing neuronal mechanisms. The presented model helps to disentangle the neuronal mechanisms of brain function and guide future non-invasive stimulation protocols. Competing Interest Statement J.O.N. has received unrelated consulting fees from Nexstim Plc, and R.J.I. has been advisor and is a minority shareholder of the company. J.O.N., L.M.K., and R.J.I. are inventors on patents and patent applications on mTMS technology. The other authors declare no conflict of interest. Footnotes * The following was updated: 1. Discussion: We clarify that the similar MEP latencies at 0 and 180 degrees of stimulus orientation seem to be associated with intrinsic characteristics of the near-rectangular biphasic E-field waveform.